OPERATIVE CORRECTION OF AIRCRAFT TRAJECTORIES BASED ON AIRBORNE WEATHER RADARS INFORMATION - Averyanova, Yuliya; Rudiakova, Anna; Yanovsky, Felix (Proceedings of National Aviation University (archive), 2020)
Trajectory prediction and optimization capabilities are considered as crucial part for efficient Air Traffic Management (ATM) operation. One of the key factors that influence onto trajectory prediction is weather situation at the departure and arrival points and along the flight route. In this context it is important to utilize widely systems of operative obtaining information about weather hazards for short-term flight trajectory correction. Airborne weather radars (AWR) are powerful and convenient tool for operative data obtaining during the aircraft flight when atmospheric and weather disturbances arise. In this paper possibilities of trajectory correction by providing accurate and operative meteorological data using the onboard radar system are shown and discussed.